Model of Smart Parking System Based On Internet Of Things - Wibby Aldryani Astuti Praditasari; Ikhwanul Kholis (Spektral, 2021)
Over increased automotive industry is being challenged to produce better quality products with intelligent innovations and lower cost. The Huge demand of the market is to get public parking area. The aim of this paper provides the highest quality equipment integrated by Smart Parking System Model. The model Provides simplify to controlling and monitoring of the parking area available which is connected to the Internet network, monitoring can be done remotely. Testing and data collection conducted in Jakarta by taking the data 24 hours during 6 months without stopping. The experiment result shows that the classification of availability of parking is approximately 78%. The results of the car sensor testing can be controlled in accordance with the parking area.   Keywords:  car, controlling, Internet of Things, monitoring, Smart Parking System